The potential of advancing endodontic practice with chitosan: its role as a sea-derived natural irrigant : Potensi kemajuan praktik endodontik dengan chitosan: perannya sebagai irigan alami yang berasal dari laut - Tharisya Amiharna Kayla; Nurul Annisa Rachman; Muhammad Akira Takashi Dharma (Makassar Dental Journal, 2026)
Chitosan is a cationic polyaminosaccharide that can be chemically modified and holds great potential in endodontic applications. Its biological and physico-chemical properties, such as cross-linking ability, antimicrobial activity, and metal ion-binding capacity, support its use as a root canal irrigant. In both stan-dalone form and in combination with sodium hypochlorite and EDTA, chitosan has proven effective in removing the smear layer and inhibiting biofilm forma-tion. This study aims to evaluate the effectiveness of chitosan as an alternative root canal irrigant in supporting the success of endodontic therapy. Many re-sults indicate that chitosan shows promising potential as an irrigating agent due to its ability to combine chelating and antimicrobial effects without causing adverse effects on dentin structure. Therefore, chitosan deserves consideration as an alternative irrigant in modern endodontic practice.